Pragmatics in Context: Contemporary Approaches to Speech Acts and Implicatures - Amina Noor; Asma Khattak; Azka Waheed; Eeman Mirza (`, 2025)
Pragmatics as a fundamental field of linguistics studies how meaning is constructed not only through linguistic forms but also through the context, speaker intention and shared knowledge. In this context, the speech act theory and implicatures have been the main focus on how language works in practice. Modern theories of speech acts focus on their contextual and dynamic character, shifting the classical Austin-Searle model to take into consideration sociocultural factors, power relations and online communication settings. Likewise, implicature has grown in the study of neo-Gricean pragmatics, relevance theory, and cognitive-pragmatic models, which emphasize the interpretation processes through which hearers arrive at the unspoken meanings. Multimodality, politeness strategies, and intercultural variation is also an aspect that has been highlighted in the current scholarship as far as creation of pragmatic meaning is concerned. In addition, online chats, social media communication and computer-mediated communication are forms of digital discourse that have reinterpreted the realization and interpretation of speech acts and implicatures within technologically mediated contexts. Such tendencies are indicative of a more holistic and context-sensitive perspective of pragmatics, where the study of pragmatics incorporates considerations of sociolinguistics, cognitive science, and communication studies. This paper will argue that pragmatics offers crucial resources to comprehend both the established spoken communication and the emerging forms of human communication in various sociocultural and digital environments based on an analysis of the recent theoretical approaches and practical contexts. This kind of exploration leads to a deeper comprehension of how the process of meaning negotiation occurs, how social relationships are sustained and how norms of communication adjust to the dynamic environment. Keywords: Pragmatics, Speech Acts, Implicature, Neo-Gricean Pragmatics, Relevance Theory, Context, Digital Communication, Politeness, Multimodality, Intercultural Communication.